A spatial gradient analysis of urban Red-tailed Hawk nestling diet. Issue 1 (24th December 2022) - White, Justin H; Snook, Joshua; Ormsby, Zachary E; Nussear, Kenneth E
Abstract: We examined Red-tailed Hawk ( Buteo jamaicensis ) nestling diets in Reno and Sparks, NV, USA during the 2015 and 2016 breeding seasons. Field researchers and nest cameras recorded 1348 prey items spanning 28 species at 88 nests. Prey consisted of 86% mammalia, 10% aves and 4% reptilia. Differential prey selection occurred among the population and at individual nests relative to an expected diet. Diet breadth differed between nests and increased with urban density. Avian prey consumption increased relative to mammalian and reptilian prey in impervious areas. When prey items were plotted on a continuous urban density spectrum, mammalian prey increased in the suburban areas and decreased toward the urban core and was inversely correlated with avian prey. Mammalian prey consumption increased and decreased at the end of April and in mid-May before increasing through the remainder of the breeding season (mid-June). Avian prey consumption peaked in May and increased through the season, and reptilian prey varied little. The geographic patterns of prey species consumed in our study reflect those in cities elsewhere. As the urban area changes, we predict that the densest populations of Red-tailed Hawks will continue to reside in the suburban areas where prey diversity and abundance are highest. This was one of the first studies to record urban Red-tailed Hawk diet and revealed patterns in how an urban population used food resources.